Braking bad – Ergonomic design and implications for the safe use of shared E-scooters. (August 2021) - Siebert, Felix Wilhelm; Ringhand, Madlen; Englert, Felix; Hoffknecht, Michael; Edwards, Timothy; Rötting, Matthias
Highlights: 2972 shared e-scooter riders were observed and 156 interviewed in Berlin, Germany. E-scooter brake systems differ in lever-wheel-coupling & ergonomics betw. providers. Observed brake readying behavior shows preference for left hand brake. Other brakes are sign. less often ready, indicating an effect of brake ergonomics. Riders lack knowledge about laws & admit illegal behavior (drink driving, dual use). Abstract: Shared e-scooters are introduced as a new form of mobility around the world. Alongside this rise in micromobility, e-scooter crashes are reported, and e-scooter riders are injured and killed in traffic. Little research has been conducted on the relation between ergonomics and the safe use of e-scooters, and it is unclear whether e-scooter riders know about prevailing e-scooter related regulation and if they adhere to existing regulation in traffic. We conducted a field observation ( n = 2972) in combination with a questionnaire survey ( n = 156), to investigate the influence of ergonomics on the safe use of shared e-scooters, and to explore riders' knowledge and self-reported behavior. Riders' brake readiness, dual use (two riders per vehicle), and helmet use was registered, and specific knowledge about the braking system of e-scooters was assessed, alongside knowledge about road rules and reported past safety related behavior. Results reveal a clear effect of braking system design, with significantly more riders readying the left hand brake, in comparison with the right hand or foot brake (depending on the e-scooter model). This was found regardless of the brake-lever-to-wheel coupling, indicating that the preference for the left hand brake can be detrimental to targeted braking of the front or rear wheel. Only one third of respondents could correctly identify the basic braking system of the shared e-scooter they had last used. In addition, high shares of illegal behavior were reported by riders. Implications of these findings for the safe operation of e-scooters, their ergonomic design, and road safety regulation are discussed.